COMPARATIVE WOOD ANATOMICAL PROPERTIES OF GENUS SYZYGIUM (FAMILY MYRTACEAE) FROM MANIPUR, INDIA - Mahesh Wangkhem; Madhubala Sharma; Chaman Lal Sharma (Indonesian Journal of Forestry Research, 2020)
COMPARATIVE WOOD ANATOMY OF GENUS SYZYGIUM (FAMILY MYRTACEAE) FROM MANIPUR, INDIA. Syzygium belongs to family Myrtaceae and comprises of mostly trees and a few shrubs.  The main objectives were   to study   anatomical and physical characteristics of five Syzygium species namely Syzygium cumini, Syzygium fruticosum, Syzygium jambos, Syzygium nervosum and Syzygium praecox and to see intra and inter species variation among them. The wood samples were taken at breast-height from straight bole and uniform crowned trees. The present study showed that all the selected species shared common features like simple perforation plate, vestured inter-vessel pits, vessel-ray pits, disjunctive ray parenchyma cells, diffuse, diffuse-in-aggregate, vasicentric, aliform and confluent types of axial parenchyma Diffuse porous and indistinct fruticosum were observed. The vessels were mostly barrel shaped with small or long tails at one or both ends in all species except tube shaped in S. jambos and drum shaped in S. fruticosum. Spiral thickenings were present in the tails of S. nervosum and S. fruticosum. Fibres were thin walled and non-septate. Occasional septate fibres and vasicentric tracheids were present in S. nervosum and S. jambos. Crystals in ray of S. nervosum and S. fruticosum and silica bodies in axial parenchyma of S. jambos were observed. The fibre percentage and wood density were maximum in S. jambos whereas moisture content was minimum in S. jambos. Principal Component Analysis revealed a close relationship among all species. Therefore, the qualitative characteristics and all quantitative anatomical characteristics can be used for reliable identification of Syzygium species.